Effects of lisdexamfetamine and s-citalopram, alone and in combination, on effort-related choice behavior in the rat - Yohn, Samantha E.; Lopez-Cruz, Laura; Hutson, Peter H.; Correa, Merce; Salamone, John D. (Psychopharmacology, 2016)
Rationale Effort-related motivational symptoms, such as anergia, psychomotor retardation, and fatigue, are an important aspect of depression and other disorders. Motivational symptoms are resistant to some treatments, including serotonin transport (SERT) inhibitors. Objectives Tests of effort-based choice using operant behavior tasks (e.g., concurrent lever pressing/ chow feeding tasks) can be used as animal models of motivational symptoms. Tests of effort-related choice allow animals to choose between high-effort actions that lead to more highly valued rewards vs. low-effort alternatives that lead to less valued rewards (i.e., less preferred or lower magnitude). Rats treated with the vesicular monoamine transport inhibitor tetrabenazine, or the cytokine interleukin-1β (IL-1β), which are associated with depressive symptoms in humans, can alter effort-related choice, reducing selection of the high effort alternative (lever pressing) while increasing intake of freely available chow. Methods The present studies focused upon the ability of lisdexamfetamine (LDX) to increase exertion of effort in rats responding on effort-based choice tasks under several different conditions. Results LDX attenuated the shift from fixed ratio 5 lever pressing to chow intake induced by tetrabenazine and IL-1β. In contrast, the SERT inhibitor s-citalopram failed to reverse the effects of tetrabenazine. When given in combination with tetrabenazine+s-citalopram, LDX significantly increased lever pressing output compared to tetrabenaine+citalopram alone. LDX also increased work output in rats responding on a progressive ratio/chow feeding choice task. Conclusions LDX can increase work output in rats responding on effort-based choice tasks, which may have implications for understanding the neurochemistry of motivational symptoms in humans.